Sustainable supply chains : A research-based textbook on operations and strategy - Bouchery, Yann; Corbett, Charles J.; Fransoo, Jan C.; Tan, Tarkan (Switzerland Springer, 2017)
Contents: Measuring environmental impacts in supply chains; Operational aspects of sustainable supply chains; Business models and strategy in sustainable supply chains; The social dimension of sustainable supply chains.
Includes bibliography and index
Keywords: Quản trị Logistics và chuỗi cung ứng